Effect of taping on functional ankle stability in female elite handball players - Soerensen, H.; Soegaard, L.; Knudsen, I. Y.; Andreasen, C. B. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
20% of all sports injuries are related to the ankle joint (Bahr, 2002); in handball the ankle is involved in 40% of all injuries, and females are considerably more injury prone than males (Lindblad et al., 1992). Self reported functional ankle instability (FAI) has been linked to increased injury risk (Ross & Guskiewicz, 2004). Likewise, FAI has been linked to reduced postural stability (PS) quantified from force plate data (Noronha et al., 2006). Taping is frequently used to prevent ankle injuries. The effect has not been investigated directly, but the effect on PS has been tested with equivocal results in studies using static, one legged stance (Bennel & Goldie, 1994; Leanderson et al., 1996). Recently, more functional methods for testing dynamic PS has been developed and validated (Ross & Guskiewicz., 2004), but hitherto not employed to study the effect of taping in players with FAI. Thus, the purpose of this study is to assess the effect of taping on dynamic PS in elite female handball players, and to detect a possible relation between the effect of taping and the severity of FAI. Methods: Fourteen female elite handball players with FAI performed standardised horizontal jumps with and without tape in randomised order. The subjects were required to stabilize as fast as possible after a one legged landing on a force plate. Time to stabilization (TTS) was calculated and used as a quantitative measure of dynamic PS. The jump, data acquisition and TTS calculation were slightly modified from Ross & Guskiewicz (2004). Results: We found no significant (p=0.075) difference in TTS values obtained with and without tape. The values were actually (nonsignificantly) higher (i.e. less stability) with tape, in agreement with Ross et al. (personal communication). Further, we found no correlation (r=0.008, p=0.979) between the effect of tape (TTS difference with and without tape) and severity of FAI (TTS value without tape). Discussion: Without prospective studies directly investigating taping`s effect on injury risk, we only have studies linking PS to injury risk and studies like the present investigating taping`s effect on PS. Since we found no reduction in TTS, the widespread use of taping among athletes might not be warranted. A possible stability reduction might even suggest that taping interferes negatively with sensori-motor functions necessary for stability.